2016
DOI: 10.1590/1983-40632016v4637959
|View full text |Cite
|
Sign up to set email alerts
|

Mineral, protein and nitrate contents in leaves of Pereskia aculeata subjected to nitrogen fertilization

Abstract: Considering that nitrogen is directly related to leaf protein content, the nitrogen fertilization in Pereskia aculeata plants may affect the protein content and increase its nutritional potential. This study aimed at assessing the effect of nitrogen fertilization on mineral, protein and nitrate contents, as well as the yield of P. aculeata leaves. A randomized blocks design was used, with three replications and five treatments, consisting of increasing topdressing nitrogen doses (0-400 kg ha-1), in soil with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
0
10
0
3
Order By: Relevance
“…In leaf sampling in all the locations, the upper middle third of the plant was considered, selecting healthy branches from the cardinal points around the plant, according to the procedures applied to vegetables in general (Malavolta et al 1997;Souza et al 2016). After that, two cuts were made, one at the fourth or fifth leaf from the tip of the plant and another at approximately 10 cm above the bifurcation of the branches.…”
Section: Soil Leaf and Root Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…In leaf sampling in all the locations, the upper middle third of the plant was considered, selecting healthy branches from the cardinal points around the plant, according to the procedures applied to vegetables in general (Malavolta et al 1997;Souza et al 2016). After that, two cuts were made, one at the fourth or fifth leaf from the tip of the plant and another at approximately 10 cm above the bifurcation of the branches.…”
Section: Soil Leaf and Root Samplesmentioning
confidence: 99%
“…There is little in the literature on management practices for this crop. Souza et al (2016) observed that different application rates of nitrogen fertilization on OPN did not show any effect on plant protein content, but they explained this result by the fact that the only type of soil they tested in the experiment had high organic matter content. The high protein content found in this species is generally common to plant species that form symbiosis with N 2 -fixing bacteria, such as leguminous plants.…”
Section: Introductionmentioning
confidence: 98%
“…Its natural habitat is the tropical forest, but it can be grown domestically in rural and urban areas (Souza et al, 2016a). P. grandifolia and P. aculeata are perennial plants that have mucilaginous leaves and present different colour of their flowers: in P. aculeata the flower is white ( Figure 1c) and in P. grandifolia is pink (Figure 1d) (Kinupp and Lorenzi, 2014).…”
Section: The Genus Pereskiamentioning
confidence: 99%
“…Leaves of P. aculeata are consumed as a vegetable, although its fruit is also edible (Souza et al, 2016a). The leaves present high levels of protein and minerals (Takeiti et al, 2009;Almeida Filho and Cambraia 1974), and hydrocolloids (Conceição et al, 2014;Lima Junior et al 2013).…”
Section: Nutritional Compoundsmentioning
confidence: 99%
“…Pouca literatura sobre o manejo dessa cultura é encontrada. Souza et al (2016) observaram que diferentes doses de adubação nitrogenada em OPN não mostraram nenhum efeito nos teores de proteína na planta, mas justificaram ao fato de que o solo testado tinha alto teor de matéria orgânica. Brasil (2010) menciona que a ora-pro-nóbis encontra-se localizada com maior tradição cultural em algumas localidades brasileiras como é o caso do município de Sabará, no estado brasileiro de Minas Gerais, onde esta espécie faz parte dos hábitos alimentares da população e das manifestações culturais como a realização anual do -Festival do Ora-pro-nóbis, que entre outros, promove e divulga a gastronomia tradicional da região.…”
Section: Introductionunclassified